A double‐tuned 1H/23Na resonator allows 1H‐guided 23Na‐MRI in ischemic stroke patients in one session. (29th June 2015) - Neumaier‐Probst, Eva; Konstandin, Simon; Ssozi, Judith; Groden, Christoph; Hennerici, Michael; Schad, Lothar R.; Fatar, Marc
Abstract : Background: Established imaging methods are still not confident in the determination of stroke onset. Sodium imaging in animal models and lately in humans implicates that the sodium signal intensity within the ischemic lesion increases in a time‐dependent fashion. Sodium imaging usually requires a time‐consuming change of resonators or magnetic resonance imaging systems. To avoid this, we used a double‐tuned 1 H/ 23 Na birdcage head coil in combination with a protocol minimizing T 1 ‐ and T 2 *‐weighting effects for measurement of sodium intensity in acute stroke patients. Methods: Multinuclear 1 H/ 23 Na data sets were obtained from 16 stroke patients [75 ± 9·9 (standard deviation) years old] 4–130 h after symptom onset. The protocol was acquired on a clinical 3T magnetic resonance imaging site using a double‐tuned 1 H/ 23 Na birdcage head coil. Sodium signal intensity within the lesion and homologous contralateral side was measured and compared. Results: With an acquisition time of the complete magnetic resonance imaging protocol of 22 min, a nonlinear sodium signal intensity increase within the lesion over time after stroke onset was acknowledged. Onset time within six‐hours showed an increase of only 8% or less, whereas onset time beyond 8·5 h demonstrated increases of 36% or more reaching a maximum of 170% > 120 h. In addition, some patients showed a difference in sodium signal intensity compared with diffusion weighted imaging lesion. Conclusions: The use of a double‐tuned 1 H/ 23 Na birdcage head coil in a clinical setting 'allowed sodium intensity measurements' in a justifiable time also for acute stroke patients, and heterogenous sodium signal intensity in the diffusion weighted imaging lesion might represent differences in tissue damage or repair.